Analysis of Forest Governance in Far-Western Terai Region of Nepal - Pant, Keshab Raj (Contemporary Research: An Interdisciplinary Academic Journal, 2021)
To explore the status of governance in Community Forestry (CF) user groups (CFUGs) in Far- Western Terai region of Nepal, six community forest user groups were selected from Kailali and Kanchanpur districts considering ethnicity, gender, size of households and accessibility. UNESCAP’s eight criteria of good governance and their respective local indicators were employed to explore the governance status of CF. Direct observation; key informant’s survey, focus group discussion and household interview with questionnaire format were used to collect the primary data where secondary data were collected from operational plan of CFUGs and other published literatures. Simple mathematical procedures were used to analyze the data. The study findings show that overall governance level is very good in women managed CFs then mixed managed CFs as well as the relationships of governance with economic activities and ethnic composition of community. This study also shows that women managed CFs is more transparent and responsive to users. Which shows that the fairness in responsibility in woman managed CF is very good and their executive committee was more responsive to their users and disadvantaged groups.